(untitled) (Asian Journal of Medical and Biological Research, 2022)
This research work was designed to ensure the production of quality Foot and Mouth Disease (FMD) vaccine. For ensuring the standard quality of vaccine, it is important to propagate the FMD Virus (FMDV) into the cell line. Tissue Culture Infective Dose50 (TCID50) assay was used to determine the biological titer of FMD virus serotypes. Baby Hamster Kidney-21 (BHK-21) Monolayer cell and BHK-21 Clone 13 Suspension cell were used to determine the TCID50 of FMDV. The result for calculating TCID50 under Monolayer cell showed that the highest biological titer of O, A, Asia-1 serotype were 10-9.83/ml, 10-9.36/ml and 10-9.70/ml respectively. On the other hand, the result for calculating TCID50under BHK-21 Clone 13 suspension cell of O, A, Asia-1 serotypes were10-6.66,10-6.50and 10-6.50/ml respectively. BHK-21 cell line, either the monolayer or the suspension cell culture system were used in FMD vaccine production to ensure the potency and the quality of the vaccine to be produced.BHK-21 monolayer cell sub-cultured by applying roller cell culture cultivation system and BHK-21 clone 13 suspension cell sub-cultured by using suspension cell culture cultivation system. Suspension culture of BHK-21 cells allows large-scale virus propagation and cost-efficient vaccine production by using Bioreactor with capacity of 50 liters maintaining biosafety and biosecurity. Asian J. Med. Biol. Res. 2022, 8 (2), 63-68